Board members' influence on resource investments to start-ups and IPO outcomes: Does prior affiliation matter? - Mathew,Prem; Takahashi,Hidenori; Yamakawa,Yasuhiro (Pacific-Basin Finance Journal, 2018)
Using data that contains career paths of start-up board members, we examine how their prior affiliations with various types of venture capital (VC) firms promote financial and human resource investments from the affiliated VC firm. We find that the likelihood of affiliation-based resource investments such as financing and board member engagement depends on the type of VC firms (e.g., bank-affiliated, corporate). Meanwhile, we find little evidence that affiliation-based resource investments lead to lower IPO costs and better post-IPO performances (i.e., return on assets, buy-and-hold abnormal returns, and failure rate). While prior affiliation could improve the inflow of resources, it might worsen screening and monitoring activities.
Keywords: Finance